1
$\begingroup$

Find the general solution of: $$\tan (\theta) + \tan (2\theta) = \tan (3\theta)$$

My Attempt: $$\tan (\theta) + \tan (2\theta) = \tan (3\theta)$$ $$\dfrac {\sin (\theta)}{\cos (\theta)}+ \dfrac {\sin (2\theta)}{\cos (2\theta)}=\dfrac {\sin (3\theta)}{\cos (3\theta)}$$ $$\dfrac {\sin (\theta+2\theta)}{\cos (\theta) \cos (2\theta)}=\dfrac {\sin (3\theta)}{\cos (3\theta)}$$

$\endgroup$
  • $\begingroup$ by general solution, you mean what is $\theta$? $\endgroup$ – John Glenn Apr 7 '18 at 7:19
3
$\begingroup$

\begin{align} \tan (\theta) + \tan (2\theta) &= \tan(3\theta) \\ \tan (\theta) + \tan (2\theta) &= \tan(\theta + 2\theta) \\ \dfrac{\tan (\theta) + \tan (2\theta)}{1} &= \dfrac{\tan(\theta) + \tan(2\theta)} {1-\tan (\theta) \tan (2\theta)} \\ \end{align}

So, either $\tan (\theta) + \tan (2\theta)=0$, or $\tan (\theta) = 0$, or $\tan (2\theta)=0$

\begin{align} \tan(\theta) + \tan(2\theta) &= 0 \\ \tan(\theta) + \dfrac{2 \tan(\theta)}{1 - \tan^2(\theta)} &= 0 \\ 3 \tan(\theta) - \tan^3(\theta) &= 0 \\ \tan(\theta) &\in \{0, \pm \sqrt 3\} \end{align}

So $\theta \in \left\{ n\pi, \pm\frac 13\pi + n\pi, \pm\frac 14\pi + n\pi : n \in \mathbb Z \right\}$

$\endgroup$
  • $\begingroup$ $$\tan2\theta=\tan(-\theta)\implies2\theta=n\pi-\theta$$ But what if $\tan2\theta=0$ and $\tan\theta\ne0?$ $\endgroup$ – lab bhattacharjee Apr 7 '18 at 12:41
  • $\begingroup$ Since $\tan(2\theta)=\dfrac{2 \tan(\theta)}{1-\tan^2(\theta)}$, then that can't happen. $\endgroup$ – steven gregory Apr 7 '18 at 14:57
  • $\begingroup$ What if $\theta=n\pi+\dfrac\pi2$ $\endgroup$ – lab bhattacharjee Apr 8 '18 at 1:16
  • $\begingroup$ Then $\tan \theta = \infty$ $\endgroup$ – steven gregory Apr 8 '18 at 2:11
  • $\begingroup$ and $$\tan2\theta=?$$ $\endgroup$ – lab bhattacharjee Apr 8 '18 at 5:30
1
$\begingroup$

Check if one of $\cos\theta,\cos2\theta,\cos3\theta=0$

Else we have $$\sin3\theta(\cos3\theta-\cos\theta\cos2\theta)=0$$

What if $\sin3\theta=0?$

Else use $$2\cos\theta\cos2\theta=\cos3\theta+\cos\theta$$

$\endgroup$
0
$\begingroup$

I'll give a hint to get you started which is that $\text{tan}(a + b) = \dfrac{\text{tan}(a) + \text{tan}(b)}{1-\text{tan}(a)\text{tan}(b)}$.

$\endgroup$
  • $\begingroup$ @ user2888499, what formula is that? $\endgroup$ – pi-π Apr 7 '18 at 5:07
  • $\begingroup$ @blue_eyed_... Sorry I had a typo that has been fixed. It's the tangent addition formula. $\endgroup$ – user2888499 Apr 7 '18 at 5:10
  • $\begingroup$ Whatever the correct formula may be that is clearly wrong. $\endgroup$ – marty cohen Apr 7 '18 at 5:11
  • $\begingroup$ @martycohen I don't see how this is wrong. I have checked it again for any errors. $\endgroup$ – user2888499 Apr 7 '18 at 5:13
  • $\begingroup$ @martycohen The only mistake I see is typesetting "tan" as \text{tan} instead of just \tan. The math is correct. $\endgroup$ – Misha Lavrov Apr 7 '18 at 5:15

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.